Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1982
DOI: 10.1159/000145545
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebellar Arteries: Cortical Patterns and Vascularization of the Cerebellar Nuclei

Abstract: This paper reports an anatomical study of the vascular supply in 60 human cerebelli from subjects of both sexes, aged between 20 and 60 years, who had died of various accidental causes. The origin, branching pattern and cortical and central distributions of the cerebellar arteries have been studied by gross dissection, vascular injection and corrosion procedures. Variations of the normal pattern of the cerebellar arteries in both origin and cortical distribution are frequently found, the anterior inferior and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 7 publications
(9 reference statements)
2
19
2
Order By: Relevance
“…Small perforating arteries branch off from the circumferential arteries to penetrate the cerebellum. Anastomoses between the circumferential arteries of PICA, AICA and SCA are constantly present among individuals [7,8]. …”
Section: Anatomymentioning
confidence: 99%
“…Small perforating arteries branch off from the circumferential arteries to penetrate the cerebellum. Anastomoses between the circumferential arteries of PICA, AICA and SCA are constantly present among individuals [7,8]. …”
Section: Anatomymentioning
confidence: 99%
“…In the human, it has been indicated that nucleus lateralis cerebelli and the other nuclei are supplied by the rhomboidal artery, which is the innermost branch of the superior cerebellar artery (Icardo et al, 1982). However, the rhomboidal artery is not defined in the Nomina Anatomica Veterinaria (International Committee on Veterinary Gross Anatomical Nomenclature, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The rhomboidal artery arises from the inner side of the superior cerebellar artery and then, following the crus cerebelli rostralis, it enters the cerebellum and gives off 2-4 branches. It supplies blood mainly to the nucleus lateralis cerebelli and the other nuclei (Icardo et al, 1982).…”
mentioning
confidence: 99%
“…Anastomoses between peripheral branches of the PICA, AICA, and SCA are consistently present among individuals [13,15,16]. The territory perfused by the AICA varies in reciprocity with the PICA and SCA [13,16]. It may be confined to the anterior surface, but the AICA may also supply lateral portions of the posterior and/or superior surface of the cerebellum (Fig.…”
Section: Anatomymentioning
confidence: 99%